Abstraction-based control for not necessarily closed behaviours - Moor, Thomas; Schmidt, Klaus; Wittmann, Thomas Karl (18th IFAC World Congress, 2011)
Keywords: ω-languages; Abstraction-based synthesis; Discrete event systems; Supervisory control

Abstraction Based Supervisory Control for Non-Regular ∗-Languages - Triska, Lukas; Moor, Thomas (16th IFAC Workshop on Discrete Event Systems, 2022)

A discussion of fault-tolerant supervisory control in terms of formal languages - Moor, Thomas (Annual Reviews in Control, 2016)
A system is fault tolerant if it remains functional after the occurrence of a fault. Given a plant subject to a fault, fault-tolerant control requires the controller to form a fault-tolerant closed-loop system. For the systematic design of a fault-tolerant controller, typical input data consists of the plant dynamics including the effect of the faults under consideration and a formal performance requirement with a possible allowance for degraded performance after the fault. For its obvious practical relevance, the synthesis of fault-tolerant controllers has received extensive attention in the literature, however, with a particular focus on continuous-variable systems. The present paper addresses discrete-event systems and provides an overview on fault-tolerant supervisory control. The discussion is held in terms of formal languages to uniformly present approaches to passive fault-tolerance, active fault-tolerance, post-fault recovery and fault hiding.
Keywords: Active fault-tolerant control; Discrete-event systems; Fault-hiding approach; Fault-tolerant control; Passive fault-tolerant control; Post-fault recovery; Supervisory control

A hierarchical and modular control architecture for sequential behaviours - Agethen, Christine; Moor, Thomas (Discrete Event Dynamic Systems: Theory and Applications, 2015)
This paper develops a hierarchical and modular control architecture for so called sequential behaviours, i.e. for plant dynamics and specifications that are represented as formal languages of infinite-length words. Our main result is the elaboration of structural properties that allow for abstraction based controller design and that are preserved under closed-loop composition. Thus, we propose to alternate controller design, closed-loop composition and abstraction in order to construct a hierarchical control system in a bottom-up fashion. When the overall plant is composed from a number of components, our approach naturally extends to the alternation of controller design, closed-loop composition, abstraction and component composition. Technically, our results are based on the notion of input-output systems known from behavioural systems theory, with a particular focus on liveness properties represented as sequential behaviours that are not necessarily topologically closed.
Keywords: Discrete-event systems; Hierarchical control systems; Modular control systems; Sequential behaviours; ω-languages

A hierarchical control architecture for sequential behaviours - Agethen, Christine; Baier, Christine; Moor, Thomas (11th International Workshop on Discrete Event Systems, WODES 2012, 2012)
Keywords: ω-languages; Discrete-event systems; Hierarchical control; Sequential behaviours

An Efficient Algorithm for the Computation of the Controllability Prefix of (*)-Languages - Moor, Thomas; Schmidt, Klaus Werner; Schmuck, Anne-Kathrin (IFAC PAPERSONLINE, 2020)
CRIS-Team WoS Importer:2021-06-25

Applied supervisory control for a flexible manufacturing system - Moor, Thomas; Schmidt, Klaus; Perk, Sebastian (10th International Workshop on Discrete Event Systems, WODES 2010, 2010)
Keywords: Discrete event systems; Implementation; Manufacturing system; Supervisory control

A Reactive Synthesis Approach to Supervisory Control of Terminating Processes - Schmuck, Anne-Kathrin; Moor, Thomas; Schmidt, Klaus Werner (IFAC PAPERSONLINE, 2020)
CRIS-Team WoS Importer:2021-06-25

Behaviour Equivalent Max-Plus Automata for a Class of Timed Petri Nets - Triska, Lukas; Moor, Thomas (15th IFAC Workshop on Discrete Event Systems, 2020)

Behaviour equivalent max-plus automata for timed petri nets under open-loop race-policy semantics - Triska, Lukas; Moor, Thomas (Discrete Event Dynamic Systems: Theory and Applications, 2021)
Timed Petri nets and max-plus automata are well known modelling frameworks for timed discrete-event systems. In this paper we present an iterative procedure that constructs a max-plus automaton from a timed Petri net while retaining the timed behaviour. Regarding the Petri net, we essentially impose three assumptions: (a) the Petri net must be bounded, i.e, the reachability graph must be finite; (b) we interpret the Petri net with single server semantics; and (c) the Petri net operates according to the race policy, i.e., the earliest possible transition will fire and thereby possibly consume tokens required by other competing transitions. Under these assumptions we show that the proposed procedure terminates with a finite deterministic max-plus automaton that realises the same timed behaviour as the Petri net. As a variation of the plain race policy, we also consider that a subsequently designed supervisor may temporarily disable distinguished transitions. Again, we present a terminating procedure that constructs a behaviour equivalent deterministic max-plus automaton. We demonstrate by example how the latter automaton can be utilised as an open-loop model in the context of supervisor contro
Keywords: Timed discrete-event systems; Petri nets; Max-plus automata; Race policy

Compositional non-blockingness verification of finite automata with prioritised events - Tang, Yiheng; Moor, Thomas (Discrete Event Dynamic Systems: Theory and Applications, 2024)
This paper addresses the verification of non-blockingness for modular discrete-event systems, i.e., discrete-event systems that are composed from component models. For such systems, the explicit construction of a monolithic representation turns out intractable for relevant applications, since such a construction in general is of exponential cost w.r.t. the number of components. One well established approach to circumvent the need for a monolithic representation for the verification task at hand is to alternate (a) the substitution of individual components by abstractions and (b) the composition of only a small number of strategically chosen components at a time. When successful, one ends up with a single moderately sized automaton which does not represent the overall behaviour in any detail but which does block if and only if the original modular system fails to be non-conflicting. This approach is referred to as compositional verification and originates from the field of process algebra with more recent adaptations to finite automata models. The main contribution of the present study is the development of a number of abstraction rules valid for compositional verification of non-conflictingness in the presence of global event priorities, i.e., where high priority events from one component possibly preempt events with lower priority of all components.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Compositional verification; Discrete-event systems; Event priorities; Modular systems

Compositional Verification of Finite Automata under Event Preemption - Tang, Yiheng; Moor, Thomas (2021 60TH IEEE CONFERENCE ON DECISION AND CONTROL (CDC), 2021)
CRIS-Team WoS Importer:2022-05-27

Compositional Verification of Non-Blockingness with Prioritised Events - Tang, Yiheng; Moor, Thomas (IFAC PAPERSONLINE, 2022)
CRIS-Team WoS Importer:2022-12-02

Consistent abstractions for the purpose of supervisory control - Agethen, Christine; Moor, Thomas; Baier, Christine; Wittmann, Thomas Karl (52nd IEEE Conference on Decision and Control, CDC 2013, 2013)

Consistent abstractions for the supervision of sequential behaviours - Bai, Xiaoying; Moor, Thomas (56nd IEEE Conference on Decision and Control, 2017)

Controller synthesis for an I/O-based hierarchical system architecture - Perk, Sebastian; Moor, Thomas; Schmidt, Klaus (9th International Workshop on Discrete Event Systems, WODES' 08, 2008)

Deterministic Finite-Automata Abstractions of Time-Variant Sequential Behaviours - Moor, Thomas; Götz, Stefan (Workshop on Discrete Event Systems, 2018)
Keywords: behavioural systems theory; hybrid systems; Finite automaton abstractions

Distributed state estimation for hybrid and discrete event systems using l-complete approximations - Raisch, Jörg; Moor, Thomas; Bajcinca, N; Geist, S; Nenchev, V (10th International Workshop on Discrete Event Systems, WODES 2010, 2010)
Keywords: Approximations; Abstractions; Discrete event systems; Behaviours; State estimation; Hybrid systems

Fault-tolerant control of discrete-event systems with lower-bound specifications - Moor, Thomas; Schmidt, Klaus Werner; Schmidt, Klaus (5th IFAC International Workshop on Dependable Control of Discrete Systems, DCDS 2015, 2015)
Fault-tolerant control addresses the control of dynamical systems such that they remain functional after the occurrence of a fault. To allow the controller to compensate for a fault, the system must exhibit certain redundancies. Alternatively, one may relax performance requirements for the closedloop behaviour after the occurrence of a fault. To achieve fault tolerance for a hierarchical control architecture, a combination of both options appears to be advisable: on each individual level of the hierarchy, the controller may compensate the fault as far as possible, and then pass on responsibility to the next upper level. This approach, when further elaborated for discrete-event systems represented by formal languages, turns out to impose a hard lower-bound inclusion specification on the closed-loop behaviour. The present paper discusses the corresponding synthesis problem and presents a solution.
Keywords: Discrete-event systems; Fault-tolerant control; Hierarchical control; Supervisory control

Fault-tolerant supervisory control - Moor, Thomas (5th IFAC International Workshop on Dependable Control of Discrete Systems, 2015)
A system is fault tolerant if it remains functional after the occurrence of a fault. Given a plant subject to a fault, fault-tolerant control requires the controller to form a fault tolerant closed-loop system. For the systematic design of a fault-tolerant controller, typical input data consists of the plant dynamics including the effect of the faults under consideration and a formal performance requirement with a possible allowance for degraded performance after the fault. For its obvious practical relevance, the synthesis of fault-tolerant controllers has received extensive attention in the literature, however, with a particular focus on continuous-variable systems. This paper provides an overview on the synthesis of fault-tolerant controllers within the framework of supervisory control to address discrete-event systems that are adequately represented by regular languages.
Keywords: Active fault-tolerant control; Discrete-event systems; Fault-hiding approach; Fault-tolerant control; Passive fault-tolerant control; Post-fault recovery; Supervisory control

Fuzzy Hybrid Systems modeling with application in decision making and control - Boutalis, Yiannis; Moor, Thomas; Schmidt, Klaus (2012 6th IEEE International Conference Intelligent Systems, IS 2012, 2012)

LibFAUDES - an open source C++ library for discrete event systems - Moor, Thomas; Schmidt, Klaus; Perk, Sebastian (9th International Workshop on Discrete Event Systems, WODES' 08, 2008)

Local Refinement of l-complete Approximations for Supervisory Control of Hybrid Systems - Yang, Jung-Min; Moor, Thomas; Raisch, Jörg (Workshop on Discrete Event Systems, 2018)
Keywords: discrete event systems; l-complete approximations; Hybrid systems; supervisory control; local refinement

Nonblocking hierarchical control of decentralized discrete event systems - Schmidt, Klaus; Moor, Thomas; Perk, Sebastian (IEEETransactions on Automatic Control, 2008)
Keywords: Decentralized control; Discrete event systems (DES); Hierarchical control; Large-scale systems; Supervisory control

On the Relation between Reactive Synthesis and Supervisory Control of Input/Output Behaviours - Schmuck, Anne-Kathrin; Moor, Thomas; Majumdar, Rupak (Workshop on Discrete Event Systems, 2018)

On the relation between reactive synthesis and supervisory control of non-terminating processes - Schmuck, Anne-Kathrin; Moor, Thomas; Majumdar, Rupak (Discrete Event Dynamic Systems-Theory and Applications, 2019)
Reactive synthesis and supervisory control theory both provide a design methodology for the automatic and algorithmic design of digital systems from declarative specifications. The reactive synthesis approach originates in computer science, and seeks to synthesise a system that interacts with its environment over time and that, doing so, satisfies a prescribed specification. Here, the distinguishing feature when compared to other synthesis problems in computer science is that the interaction is temporal in that it explicitly refers to a sequence of computation cycles. Supervisory control originates in control theory and seeks to synthesise a controller that - in closed-loop configuration with a plant - enforces a prescribed specification over time. The distinguishing feature compared to other branches of control is that all dynamics are driven by discrete events as opposed to continuous signals. While both methods apparently are closely related, the technical details differ significantly. We provide a formal comparison which allows us to identify conditions under which one can solve one synthesis problem using methods from the other one; we also discuss how the resulting solutions compare. To facilitate this comparison, we give a unified introduction to reactive synthesis and supervisory control and derive formal problem statements and a characterisation of their solutions in terms of omega-languages. Recent contributions to the two fields address different aspects of the respective problem, and we expect the formal relationship identified in this paper to be useful in that it allows the application of algorithmic techniques from one field in the other.
CRIS-Team WoS Importer:2020-01-10

Refinements of behavioural abstractions for the supervisory control of hybrid systems - Yang, Jung-Min; Moor, Thomas; Raisch, Joerg (Discrete Event Dynamic Systems-Theory and Applications, 2020)
A common approach to controller synthesis for hybrid systems is to first establish a discrete-event abstraction and then to use methods from supervisory control theory to synthesise a controller. In this paper, we consider behavioural abstractions of hybrid systems with a prescribed discrete-event input/output interface. We discuss a family of abstractions based on so called experiments which consist of samples from the external behaviour of the hybrid system. The special feature of our setting is that the accuracy of the abstraction can be carefully adapted to suit the particular control problem at hand. Technically, this is implemented as an iteration in which we alternate trial control synthesis with abstraction refinement. While localising refinement to where it is intuitively needed, we can still formally establish that the overall iteration will solve the control problem, provided that an abstraction-based solution exists at all.
CRIS-Team WoS Importer:2020-05-08

SCT-based priority-free conditionally-preemptive scheduling of modular real-time systems with exact task execution time - Wang, Xi; Li, Zhiwu; Moor, Thomas (Discrete Event Dynamic Systems-Theory and Applications, 2019)
This study presents a novel discrete-event systems (DES) modeling framework to address real-time system (RTS) with sporadic, periodic, and non-repetitive real-time tasks. Our approach is organized in three steps. First, the effect of individual timing parameters of each task, such as job arrival and deadlines, are represented by modular DES. Second, we choose the required modules for the specific RTS at hand to compose an overall model. Third, we utilize supervisory control to find all schedules that are consistent with the timing requirements of all tasks. In contrast to fixed task priorities, we address general preemption relations represented by a preemption matrix and thereby implement priority-free conditionally-preemptive (PFCP) real-time scheduling. As a particular feature of the closed-loop configuration, the schedules obtained refer to the actual job execution time as opposed to upper and lower bounds. We illustrate our approach by a real-world example in the context of an automated manufacturing system.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Best-case execution time; Conditional preemption; Real-time systems; Supervisory control; Worst-case execution time

The controllability prefix for supervisory control under partial observation with an application to fault-tolerant control - Moor, Thomas; Schmidt, Klaus Werner (20th IFAC World Congress Toulouse, 2017)

Top-Down Nested Supervisory Control of State-Tree Structures Based on State Aggregations - Wang, Xi; Moor, Thomas; Li, Zhiwu (IFAC PAPERSONLINE, 2020)
CRIS-Team WoS Importer:2021-06-25